2008
DOI: 10.1002/jsfa.3392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hot water treatment on sprouting, membrane permeability, sugar content and chip colour of reconditioned potato tubers following long‐term cold storage

Abstract: BACKGROUND: The efficacy of hot water treatment in facilitating successful reconditioning of processing potato (Solanum tuberosum L.) cultivar Hermes following 6 months cold storage at 4.5• C was examined. Tubers were subjected to hot water treatments (HWTs) at 52.5, 55.0, 57.5 and 60.0• C for 0-60, 0-50, 0-40 and 0-20 min, respectively, and then reconditioned for 20 days at 16• C before evaluated for sprouting, fresh weight loss, membrane permeability, sugar content and processing quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…According to Lurie (1998), many fruits and vegetables tolerate exposure to water temperatures of 50 to 60°C for up to 10 min. On the other hand, Kyriacou et al (2008) reported that for 'Hermes' potato tubers, 20-min exposure time was the longest safe limit for HW treatment at 57.5°C and 25 min for treatment at 55°C, suggesting the possibility that physiological age, cultivar, and pre-processing storage conditions significantly affect thermotolerance in potato tuber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lurie (1998), many fruits and vegetables tolerate exposure to water temperatures of 50 to 60°C for up to 10 min. On the other hand, Kyriacou et al (2008) reported that for 'Hermes' potato tubers, 20-min exposure time was the longest safe limit for HW treatment at 57.5°C and 25 min for treatment at 55°C, suggesting the possibility that physiological age, cultivar, and pre-processing storage conditions significantly affect thermotolerance in potato tuber.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, immersion of potatoes at water bath temperatures of 60°C or higher resulted in tuber surface blackening and rapid decay (Ranganna et al, 1998). In studies aiming to prevent sprouting of potatoes during storage, the latter authors demonstrated that the tubers can tolerate HW treatments at 57.5°C for 20 to 30 min and be safely stored for 12 weeks at either 8 or 18°C without suffering from heat damage, whereas Kyriacou et al (2008) reported that tuber tolerance at the same temperature is limited to 20 min. It would be interesting to investigate whether less severe heat treatments could reduce the accumulation of phenolics in stored fresh-cut potato slices as well as their oxidation resulting from the activity of PPO.…”
mentioning
confidence: 99%
“…Sugar analyses were performed on pellets 20 mm long taken from the centre of each tuber using a 9 mm cork borer and immersed in liquid nitrogen before being lyophilised for 48 h. Glucose, fructose and sucrose were separated using an acetonitrile/water (78 : 22 v/v) mobile phase and a Waters carbohydrate cartridge column (4.6 mm × 250 mm) (Milford, MA, USA) on a Waters high-performance liquid chromatography (HPLC) system equipped with a Model 2414 refractive index detector and Millennium 32 Chromatography Manager, as described previously. 10 The limit of detection was 250 mg kg −1 potato dry matter (dm) for both fructose and glucose and 400 mg kg −1 dm for sucrose. Tuber reducing sugar content represents the sum of glucose and fructose contents.…”
Section: Methodsmentioning
confidence: 99%
“…For tuber sugar and NO 3 ‐N analyses during storage, parenchyma pellets 20 mm long were taken from the centre of each tuber using a 9 mm cork borer, immersed in liquid nitrogen and lyophilised for 48 h. Tuber NO 3 ‐N measurements were performed with Reflectoquant ® nitrate test strips in an RQflex 16 970 reflectometer (Merck, Darmstadt, Germany) on 4 kg samples at harvest. Glucose, fructose and sucrose were separated by high‐performance liquid chromatography (HPLC) as described previously 23. Aggregate samples were extracted with 800 mL L −1 boiling ethanol and vacuum dried at 35 °C, then the residue was dissolved in 5 mL of water.…”
Section: Methodsmentioning
confidence: 99%